Neutrophils Rolling on Immobilised Platelets Migrate into Homotypic Aggregates after Activation - Rainger, G. E.; Buckley, Christopher; Simmons, David L.; Nash, Gerard B. (Thrombosis and Haemostasis, 1998)
Interactions between platelets and leucocytes are implicated in the pathology of thrombotic vascular disease. Using a flow-based adhesion assay we have investigated a novel route for the formation of neutrophil aggregates on the surface of immobilised activated platelets. Neutrophils perfused over a platelet monolayer formed numerous rolling attachments but rapidly stopped and spread after the superfusion of N-formyl-methionyl-leucyl-phenylalanine or platelet-activating factor (both at 10–7 M). Subsequent integrin-mediated migration across the platelet monolayer enabled formation of homotypic neutrophil aggregates, which was significant within 2.5 min of receipt of either stimulus. Aggregates increased in size with time and had an average projected area of ~500 μm2 after 10 min. Increasing size was correlated with an increasing tendency for movement downstream and large aggregates sometimes tumbled in that direction. The formation and stability of homotypic aggregates was dependent on several adhesive mechanisms. Antibody blockade demonstrated that interactions involving CD11a/ CD18 and ICAM-3, between αvβ3-integrin and CD31 and between L-selectin and an unidentified counter-ligand were all required for the complete aggregatory response. Furthermore, blockade of L-selectin allowed initial aggregation which then reversed, suggesting that this receptor might regulate the interactions between other adhesion molecules that directly supported cell-cell adhesion. We propose that this novel route for leucocyte aggregation could promote vascular occlusion in thrombotic vessels or at distal sites in the event of embolisation.